"Wyznania" św. Augustyna w refleksji fenomenologicznej w XXI wieku = "Confessions" of Saint Augustine in phenomenological reflection of the 21st centu - Rzymowska, Luiza (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper begins with a brief overview of the influence of St. Augustine`s writings upon the Christian thought. Subsequently, the subject is developed in three parts. The first part focuses on the importance of the research of Natalie Depraz for the contemporary reading of the "Confessions". Depraz introduced this masterpiece of spiritual literature to the stream of phenomenological reflection in the twenty-first century.
Keywords: Augustyn z Hippony (święty Kościoła katolickiego; 354-430); Depraz, Natalie (1964- ); Husserl, Edmund (1859-1938); "Confessiones"; Christianity; philosophy; theology; phenomenology; "epoché"; belles-lettres; autobiography; narrative; rhetoric; inner experience; inner journey; conversion